The effects of flight training on flying cadets' brain structure. - Liang Wang; Chengshi Yang; Dongfeng Yan; Lu Ye; Xi Chen; Shan Ma (PLoS ONE)
In recent years, the impact of professional training on brain structure has sparked extensive research interest. Research into pilots as a high-demand, high-load, and high-cost occupation holds significant academic and economic value. The aim of this study is to investigate the effects of flight training on the brain structure and cognitive functions of flying cadets. The structural magnetic resonance imaging (sMRI) data from 39 flying cadets and 37 general college students underwent analysis using voxel-based morphometry (VBM) and surface-based morphometry (SBM) methods to quantitatively detect and compute multiple indicators, including gray matter volume (GMV), curvature, mean curvature of the white matter surface (MC-WMS), the percentage of surface white matter gray matter (WM-GM percentage), surface Jacobi (S-Jacobi), and Gaussian curvature of white matter surface (GC-WMS). At the voxel level, the GMV in the left temporal pole: middle temporal gyrus region of flying cadets significantly decreased (Gaussian random field, GRF, P < 0.05). At the surface level, there was a significant increase in curvature, MC-WMS, and S-Jacobi in the lateral occipital region of flight cadets (Monte Carlo block level correction, MCBLC, P<0.05), a significant increase in WM-GM percentage in the cuneus region of flight cadets (MCBLC, P<0.05), and a significant increase in GC-WMS in the middle temporal region of flight cadets (MCBLC, P<0.05). In addition, these changes were correlated with behavioral tests. Research suggested that flight training might induce changes in certain brain regions of flying cadets, enabling them to adapt to evolving training content and environments, thereby enhancing their problem-solving and flight abilities. By analyzing multiple indicators at the voxel and surface levels in an integrated manner, it advances our understanding of brain structure, function, and plasticity, while also facilitating a more profound exploration of the neural mechanisms within the pilot's brain.